IDENTIFIKASI PERMASALAHAN PENGANGGURAN: STUDI KASUS DI PEDESAAN (DESA SELAT, KABUPATEN KLUNGKUNG) - Suasih, Ni Nyoman Reni; Karmini, Ni Luh (Buletin Studi Ekonomi; VOL.27.NO.1.FEBRUARI 2022, 2022)
Unemployment is one of the macroeconomic problems that hinder regional development because it will cause other social problems. The phenomenon of unemployment in rural areas is a serious problem for Selat Village, Klungkung Regency. This study aims to identify conditions and factors causing unemployment, as well as labor market conditions in Selat Village. The data in this study were collected through questionnaires, interviews, and FGD techniques. Furthermore, the data were analyzed through quantitative and qualitative descriptive analysis techniques. The results of the analysis show a picture of employment in Selat Village, where the percentage of the population of working age who does not work is quite high, namely 33.85%. Although the demand for labor in Selat Village is not nearly as high as in urban areas, people who do not work are reluctant to migrate to cities. The labor market is segmented into the formal sector and the informal sector. The causes of unemployment can be classified into factors of education, skills, wages, information, and the availability of jobs. Further research is needed on Alternative Livelihoods.